حمايـة العلامـات التجارية في القانون الدولي - ميســة, عبد الوهـاب (جامعة الوادي University of Eloued, 2017)
تحتل العلامة التجارية مكانة هامة ومميزة بين حقوق الملكية الصناعية وتعتبر ركيزة في ارتقاء ونجاح المشروع الاقتصادي ولا يخفى على أحد الدور الذي تقوم به في حياة والمؤسسات الصناعية والتجارية سواء على الصعيد الوطني أو الدولي. وقد نظم المجتمع الدولي العديد من الاتفاقيات المنظمة لحماية هذه الحقوق في إطار دولي محكم يضمن حماية فعالة لها.ونظرا لاتساع نطاق التجارة وسرعة المواصلات وازدياد العلاقات التجارية لم تعد القوانين الوطنية وحدها كافية لتأمين حماية شاملة للعلامة التجارية الأمر الذي أوجد حالة ملحة في داخل إقليم مصدرها كل هذا أدي إلى التفكير في وسيلة أنجع لحماية العلامة في خارج إقليم مصدرها وكانت الاتفاقيات الدولية في هذا المضمار هي الحجر الأساس الذي اعتمدته الدول لحماية تلك العلامات وهو موضوع The brand occupies an important and distinctive position among the industrial property rights and is a pillar in the advancement and success of the economic project. It is well known that it plays a role in the life of industrial and commercial institutions both nationally and internationally. The international community has organized numerous conventions to protect these rights within an international framework that ensures effective protection. Given the wide scope of trade, the speed of transport and the increase in trade relations, national laws alone are no longer sufficient to provide comprehensive protection of the trademark, This led to the thinking of a more effective way to protect the mark in the outside of the territory of origin. The international conventions in this regard are the cornerstone adopted by States to protect those marks,
قانــون أعمــال
Keywords: حماية ،العلامة ،التجارية ،القانون ،الدولي; Protection, trademark, trade, law, international